Medeni yargılama hukukunda derdestlik - Korkmaz, Görkem (My University, 2025)
Medeni yargılama hukukunda derdestlik Medeni yargılama hukuku bakımından derdestlik, bir davanın görülmekte olduğunu, bir başka deyişle, yargılama sürecinin devam etmekte olduğunu ifade eder. Davanın açılmasının usul hukukuna ilişkin sonuçlarından biri olarak kabul edilen derdestlik, davanın açılmasıyla kendiliğinden ortaya çıkar. Yargılama neticesinde davanın esasına ya da usulüne ilişkin verilmiş olan kararın kesinleşmesi neticesinde derdestlik ortadan kalkar. Derdestliğin yargılama hukukundaki asli etkisi, HMK’nın m. 114/ 1-ı hükmünde ‘‘Aynı davanın, daha önceden açılmış ve halen görülmekte olmaması’’ şeklinde düzenlenmiş olan, derdestlik dava şartıdır. Derdestlik dava şartı, usul ekonomisinin gerçekleştirilmesi, dürüstlük kuralının ve hak arama özgürlüğünün ihlal edilmesinin engellenmesi ve çelişkili kararlar verilmesinin önlenmesi ile toplumsal barışın sağlanması hedeflerini gerçekleştirmeyi amaçlamaktadır. Olumsuz bir dava şartı olarak düzenlenen derdestlik dava şartı, mahkeme tarafından yargılamanın her aşmasında kendiliğinden inceleneceği gibi taraflar da yargılamanın her aşamasında aynı davanın daha önceden açılmış ve halen görülmekte olduğunu ileri sürebilir. Mahkemenin derdestlik dava şartı nedeniyle bir davayı reddetmesi için, öncelikle açılmış olan iki davanın bulunması, ilk davanın halen görülmekte olması ve bu iki davanın aynı dava niteliğinde olmaları gerekir. İki davanın aynı dava olarak kabul edilmesi için bu davalarda, davanın taraflarının, dava konusunun ve dava sebebinin aynı olması gereklidir. Derdestlik dava şartı nedeniyle bir davanın reddedilmesi için gereken koşulların mevcut olduğuna kanaat getiren mahkeme, davayı reddedecektir. Bu karar nihai bir karar olduğu için, bu karara karşı kanun yollarına müracaat edilebilir.

Lis pendens in civil procedural law In the doctrine of civil procedural law, lis pendens denotes the procedural status whereby an action is already under judicial examination and the adjudicatory process remains ongoing. As a procedural consequence inherently arising upon the initiation of a lawsuit, lis pendens comes into existence ipso iure at the moment of filing. This status persists until the judgment— whether rendered on the merits or on procedural grounds—acquires finality. The principal doctrinal function of lis pendens is codified in Article 114/ 1-(ı) of the Turkish Code of Civil Procedure (HMK), which articulates as a condition of admissibility that “the same action must not have been previously instituted and still pending.” This procedural requirement seeks to advance the objectives of procedural economy, safeguard the principle of good faith and the constitutional right of access to justice, prevent duplicative or contradictory adjudications, and thereby reinforce legal certainty and societal equilibrium. As a negative procedural prerequisite, lis pendens is subject to ex officio scrutiny by the court at any stage of the proceedings. Likewise, litigants retain the ability to invoke the objection of lis pendens throughout the entirety of the trial process. For a court to dismiss a claim on this ground, three cumulative criteria must be satisfied: (i) two separate actions must exist, (ii) the earlier action must remain pending, and (iii) the two actions must be identical in terms of parties, subject matter, and cause of action—criteria traditionally accepted in comparative procedural scholarship for determining the “sameness” of a claim. Where the court establishes that the conditions of lis pendens have been fulfilled, it shall dismiss the subsequent action. Such a dismissal constitutes a final procedural ruling and is therefore amenable to appellate review through the prescribed legal remedies.
Lis pendens in civil procedural law
Keywords: Aynı Dava; Civil procedure; Dava Şartları; Derdestlik; Derdestlik İtirazı; Identity of Actions; İlk İtirazlar Lis Pendens; Litigation Conditions; Medeni yargılama; Plea of Pendency; Preliminary Objections